Distribution of Single-Wall Carbon Nanotubes in the Xenopus laevis Embryo after Microinjection - Holt, Brian D. (J Appl Toxicol, 2015)
Single-wall carbon nanotubes (SWCNTs) are advanced materials with the potential for a myriad of diverse applications, including biological technologies and largescale usage with the potential for environmental impacts. SWCNTs have been exposed to developing organisms to determine their effects on embryogenesis, and results have been inconsistent arising, in part, from differing material quality, dispersion status, material size, impurity from catalysts, and stability. For this study, we utilized highly purified SWCNT samples with short, uniform lengths (145 ± 17 nm) well dispersed in solution. To test high exposure doses, we microinjected > 500 μg mL(-1) SWCNT concentrations into the well-established embryogenesis model, Xenopus laevis, and determined embryo compatibility and sub-cellular localization during development. SWCNTs localized within cellular progeny of the microinjected cells, but heterogeneously distributed throughout the target-injected tissue. Co-registering unique Raman spectral intensity of SWCNTs with images of fluorescently labelled sub-cellular compartments demonstrated that even at the regions of highest SWCNT concentration, there were no gross alterations to sub-cellular microstructures, including filamentous actin, endoplasmic reticulum and vesicles. Furthermore, SWCNTs did not aggregate or localize to the perinuclear sub-cellular region. Combined, these results suggest that purified and dispersed SWCNTs are not toxic to X. laevis animal cap ectoderm and may be suitable candidate materials for biological applications.